2007
DOI: 10.1254/jphs.cp0070034
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective Role of Glucocorticoid Hormones

Abstract: Abstract. Gastric ulcer disease remains widespread; a stressful lifestyle and nonsteroidal antiinflammatory drugs (NSAIDs) make significant contributions to this pathological situation. The findings overviewed here support the idea that glucocorticoid hormones released in response to acute stress or NSAIDs act as gastroprotective substances and exert many of the same actions in the stomach as prostaglandins (PGs) and nitric oxide (NO) as well as capsaicin-sensitive afferent neurons. Glucocorticoids exert a gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
6
0
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 28 publications
4
6
0
3
Order By: Relevance
“…We have also shown that well-known nonsteroidal antiinflammatory drugs (NSAIDs) such as indomethacin and aspirin at ulcerogenic doses induce a rise in corticosterone, which helps the gastric mucosa to resist the harmful actions of these ulcerogenic agents (Filaretova et al, 2002a, b;2005). The findings support the idea that glucocorticoids released during acute activation of the HPA axis caused by various ulcerogenic stimuli act as a gastroprotective hormone (Filaretova et al, 2001(Filaretova et al, , 2007 but not ulcerogenic ones. It is assume that adaptive action of glucocorticoid hormones released in stress conditions may also be applied to the gastric mucosa.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…We have also shown that well-known nonsteroidal antiinflammatory drugs (NSAIDs) such as indomethacin and aspirin at ulcerogenic doses induce a rise in corticosterone, which helps the gastric mucosa to resist the harmful actions of these ulcerogenic agents (Filaretova et al, 2002a, b;2005). The findings support the idea that glucocorticoids released during acute activation of the HPA axis caused by various ulcerogenic stimuli act as a gastroprotective hormone (Filaretova et al, 2001(Filaretova et al, , 2007 but not ulcerogenic ones. It is assume that adaptive action of glucocorticoid hormones released in stress conditions may also be applied to the gastric mucosa.…”
supporting
confidence: 70%
“…Accordingly our results glucocorticoid hormones released during activation of HPA axis may contribute to gastroprotection by maintaining local gastric mucosal homeostasis (Filaretova et al, 2007). The hormones may contribute to local gastric mucosal homeostasis through maintaining of general body homeostasis, including glucose and temperature homeostasis as well as systemic blood pressure, which could be a fundamental of their beneficial action on various gastric targets and, finally, on gastric mucosal integrity .…”
supporting
confidence: 51%
“…Consistently with this contention, glucocorticoid antagonists enhanced the severity of stress-induced erosions, further supporting a protective role of these hormones during stress (Filaretova et al, 2001). The mechanisms through which glucocorticoids exert their protective effects include the maintenance of glucose homeostasis, the increase in mucosal blood flow and mucus secretion, and the attenuation of both enhanced gastric motility and microvascular permeability (Filaretova et al, 2007).…”
Section: Neurohormonal Mechanismssupporting
confidence: 58%
“…In particular, 6a-methylprednisolone suppressed spontaneous healing of open wounds [35]. On the other hand, despite common evidence that use of glucocorticoids increases the risk of complicated peptic ulcer disease [7], corticosteroids were also shown to prevent stress gastric lesions in experimental animals (for a review see, e.g., [23,36]). …”
Section: Introductionmentioning
confidence: 99%